MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KECEPATAN PEMBUATAN PINTU KAYU - Nurhadiyanto, Didik; Rachmad, Suprapto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
In making wood crafting specially making of door and shutter leaf oftentimesobtained a handicapped door product at shares pen hole in the form of barst / break, the difficulty make the door leaf if market request quite a lot, and narrow tightworkplace so that needed a workbench which inuliti function so that all workable doormaking work the desk. Considering problems faced by this wood industry hence the industry require to be assisted by given a appliance of door maker in the form of a workbench of multi function provided by the appliance of hole pen maker. With the workbench all worker can finish the work of door making start from cutting of'workpiece.making 'of hole pen come up with the setting. The aim of this program is to" perform and make the workbench by means of hole pen to increase quality and time efficiency, so that small industry can do the mote order.In executing this program we take the following stages : (1) planningI workbench to produce the leaf of door or window, matching with society condition. So that this appliance easy to accepted by society hence this appliance own the following specification: Easy to operate it, economize the place, work of making of, door leaf become easier, (2) testing workbench to make door in wood industry industry "UD. W ARSIDI" to know until where the appliance perforrnace, covering ist amenity and speed finish the making of door leaf. (3) door leaf yielded from this appliance compared to by its quality with the door leaf made conventionally. (4 ) machine completiori its performance according to plan (5) delivering the machine at partner industry to be utilized so that can be productive. (6) compiling final report of activity execution, Result of inferential workbench perfomance test-drive as follows: (1) Maker of hole pen of this desk can function better. Hole diameter chisel between 9 up to IS rnm. (2) Compered to workmanship in conventionally making of hole pen with this desk is quicker till 4 times.(3) desk can be used better to reap the side goodness step aside and also wide side.(4) long desk of the size 2.03 rn, wide 0,84 rn, high 0,7Im, speed turn around the motor is 2.800 rpm, speed turn around to drill, 2.800 rpm, (5) with.this workbench, during 2 day can make 8 shutter and 2 door leaf, whereas without using workbench only can make 5 shutter and 1 door leaft (6) quality of result of work in making softer hole pen when compared to a manual work (7) efficiency of place use very high. 'Key word: workbench, hole pen, door, and window